Top-down activities to enhance listening skills among students of third year “a” of bachillerato afternoon session, at colegio de bachillerato presidente isidro ayora in loja city during the 2020-2021 school year. - Vélez Bravo, Katherine Michelle (2021)
The main goal of this research was to enhance the listening skills through the use of top-down activities of the students of the third year “A” of Bachillerato afternoon session, at Colegio de Bachillerato “Presidente Isidro Ayora” in Loja city during the 2020-2021 school year. The methods were the scientific, the analytic-synthetic, the descriptive and the statistical methods, which contributed to obtain, describe, represent, interpret, and analyze the results of the research. To collect the data, different instruments were used such as tests, questionnaires, observation sheets, and field notes which were applied to eight students. The results indicated that there was a meaningful improvement in the students’ listening skills to predict information, identify main ideas, recognize general data, and grasp specific details from audio. To sum up, the top-down activities were effective for the enhancement of students listening skills and motivated them to were active and attentive in class.